2015
DOI: 10.1007/s10856-015-5393-7
|View full text |Cite
|
Sign up to set email alerts
|

In situ synthesis of hydroxyapatite nanocomposites using iron oxide nanofluids at ambient conditions

Abstract: This paper describes a simple method for the room temperature synthesis of magnetite/hydroxyapatite composite nanocomposites using ferrofluids. The in situ synthesis of magnetic-hydroxyapatite results in a homogenous distribution of the two phases as seen both in transmission electron micrographs and assembled to a micron range in the confocal micrographs. The selected area diffraction pattern analysis shows the presence of both phases of iron oxide and hydroxyapatite. To the dialyzed ferrofluid, the constitue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…The peak at 1037 cm -1 is associated with the stretching modes of the P-O bonds of HA and the doublet at 606 cm -1 and 560 cm -1 are due to bending modes of P-O bonds in phosphate group further confirming the presence of phosphate in the system [51]. Three well defined strong peaks at 1380 cm -1 , 1645 cm -1 and 3154 cm -1 are assigned to C-N, C-O and the stretching of N-H bond respectively seen only in C-HA and B-HA due to the presence of proteins/amino acids [52]. Presence of CO 3 2group is revealed by a weak peak at 870 cm -1 in case of Bare-HA.…”
Section: Ft-ir Analysismentioning
confidence: 62%
See 1 more Smart Citation
“…The peak at 1037 cm -1 is associated with the stretching modes of the P-O bonds of HA and the doublet at 606 cm -1 and 560 cm -1 are due to bending modes of P-O bonds in phosphate group further confirming the presence of phosphate in the system [51]. Three well defined strong peaks at 1380 cm -1 , 1645 cm -1 and 3154 cm -1 are assigned to C-N, C-O and the stretching of N-H bond respectively seen only in C-HA and B-HA due to the presence of proteins/amino acids [52]. Presence of CO 3 2group is revealed by a weak peak at 870 cm -1 in case of Bare-HA.…”
Section: Ft-ir Analysismentioning
confidence: 62%
“…51 Three well-dened strong peaks at 1380 cm À1 , 1645 cm À1 and 3154 cm À1 are assigned to C-N, C-O and stretching of the N-H bond respectively, and are seen only in C-HA and B-HA due to the presence of proteins/amino acids. 52 Presence of the CO 3 2À group is revealed by a weak peak at 870 cm À1 in the case of bare-HA. To further cross-check our FT-IR results we have characterized our samples by the XPS technique, which will conclude the chemical linkage of different species present in the sample, and most importantly the interaction of the matrix with HA, which was not visible by FT-IR.…”
Section: Ft-ir Analysismentioning
confidence: 98%
“…In biomedical applications, the most commonly utilized forms of superparamagnetic iron oxide magnetic NPs, also referred to as SPIONs, are maghemite (γ-Fe 2 O 3 ) and magnetite (Fe 3 O 4 ). , SPIONs are generally well-tolerated in biological systems and are similar in size to biomacromolecules. Therefore, they are ideal substrates to be functionalized with biomolecules to produce nanobioconjugates for biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Although, many contradictory results have been published about the toxicity of superparamagnetic iron oxide nanoparticles, recently [31] reported that the surface coating large influences different cell types and the possible toxic effects vary accordingly [13]. Tartaj et al (2003) [32] [33] reported that the size, shape, and magnetic dipole moment of the particles may also play a role in in vivo experiments. The one pot biomimetic synthesis i.e.…”
Section: Discussionmentioning
confidence: 99%